2008
DOI: 10.1007/s10792-008-9281-8
|View full text |Cite
|
Sign up to set email alerts
|

Case control study of dry eye and related ocular surface abnormalities in Ibadan, Nigeria

Abstract: A close relationship exists between ocular irritation symptoms, surface abnormalities and functional evidence of tear instability. Such patients should be treated empirically or screened for dry eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Reduced corneal sensation could provide inadequate feedback through ophthalmic nerve to the central nervous system, resulting in less efferent stimulation to lacrimal gland, with reduced tear production and promotion of a vicious cycle [11]. In addition, blepharitis and other ocular surfaces disorders commonly associated with DED may also influence patient's perception of symptoms [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced corneal sensation could provide inadequate feedback through ophthalmic nerve to the central nervous system, resulting in less efferent stimulation to lacrimal gland, with reduced tear production and promotion of a vicious cycle [11]. In addition, blepharitis and other ocular surfaces disorders commonly associated with DED may also influence patient's perception of symptoms [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The examiner must visually evaluate the eyelid margin for each patient on both upper and lower eyelids with a slit lamp. Digital pressure is constantly applied to the upper and lower tarsus and, after that, the Meibomian gland and the degree of obstruction should be evaluated [26,29,31,41].…”
Section: Discussionmentioning
confidence: 99%
“…Based on OSDI score, the ocular surface is defined as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), or severe (33-100) [44]. It is noteworthy that although the OSDI is not routinely used in clinical practice, it has been shown to be valid and reliable to quantify the impact of dry eye on the quality of life [44].…”
Section: Discussionmentioning
confidence: 99%
“…10 Many investigators have reported variable agreement/concordance between the diagnostic tests for DED. [11][12][13][14][15][16][17][18][19][20][21] Although some Nigerian studies 11,12 and other reports elsewhere [13][14][15] have reported strong agreement between Schirmer test and tear-film breakup time (TBUT), reports in Australia, 4 China, 6 and elsewhere 7,[16][17][18][19] observed poor agreement between the diagnostic tests for DED. The observed lack of concordance between the DED assessment for symptoms and clinical signs in most cases makes symptom an important component of DED diagnosis, because the clinician is compelled to treat the patient based on symptoms alone.…”
mentioning
confidence: 99%
“…The few related African reports are prevalence study 25 or small sample case-control surveys. 11,12 Consequently, this study, conducted on a Nigerian tertiary adult ophthalmic outpatient…”
mentioning
confidence: 99%